Protective effect of Zataria multiflora Boiss. and its main compound, rosmarinic acid, against malathion induced oxidative stress and apoptosis in HepG2 cells. Issue 4 (3rd April 2021) - Karami-Mohajeri, Somayyeh; Najafi, Amir; Behnam, Behzad; Sadeghi Meymandi, Mitra; kashitarash Ifahani, Zahra; Jafari, Elham; Heidari, Mohmoudreza; Mohamadi, Neda; Sharififar, Fariba
Abstract: Malathion (MT) is one of the most widely used organophosphorus insecticides which induces toxicity through oxidative stress induction, free radical production and acetylcholinesterase inhibition. In this work, HepG2 cells were used to determine the effect of Zataria multiflora methanolic extract (MEZM) and rosmarinic acid (RA) on MT-induced cytotoxicity, oxidative stress, and apoptosis. Total phenolic content (TPC) and total flavonoid content (TFC) were determined and plant was further standardized based on RA content using HPLC method. The cultured HepG2 cells were pretreated with MEZM (1 μg/ml) and RA (0.1 μg/ml) for 4 h and exposed to MT (100 μM). Cell viability, oxidative stress biomarkers, ROS production, and cell death were examined after 24 h. The amount of RA was determined 73.48 mg/g dried extract. IC50 values of MEZM and MT were 368.56 μg/ml and 99.43 μM, respectively. Pretreatment with MEZM and RA decreased the cytotoxicity, oxidative stress, and cell percentage in the late apoptosis and necrosis stages induced by MT. There was no significant difference between MEZM and RA effects. The present study showed the significant protective effects of MEZM against toxicity induced by MT in hepatocytes which can be attributed to the plant antioxidant constituents including RA.